Tinjauan Yuridis Pembatalan Sertipikat Hak Milik Atas Tanah Pada Kantor Pertanahan Nasional Kabupaten Jeneponto - Suhartati; Abdul Kadir; Mahir (Pledoi Law Jurnal, 2025)
ABSTRACT: This research aims to examine the juridical review of the cancellation of land ownership certificates at the National Land Office of Jeneponto Regency. The study investigates the procedure for canceling the certificate and the underlying factors that lead to such cancellation. Using a normative juridical method, supported by statutory and conceptual approaches, this study finds that the process generally begins with a legal administrative defect or court ruling with permanent legal force. Factors include procedural errors, legal subject or object errors, overlapping ownership, and enforcement of final court decisions. This research contributes to understanding the legal mechanisms that ensure land ownership legality and administrative justice. ABSTRAK: Penelitian ini bertujuan untuk mengkaji tinjauan yuridis terhadap pembatalan sertipikat hak milik atas tanah pada Kantor Pertanahan Nasional Kabupaten Jeneponto. Penelitian ini menelaah prosedur pembatalan serta faktor-faktor yang menjadi dasar terjadinya pembatalan. Dengan metode yuridis normatif dan pendekatan perundang-undangan serta konseptual, ditemukan bahwa proses umumnya diawali dari cacat hukum administrasi atau putusan pengadilan yang berkekuatan hukum tetap. Faktor-faktor tersebut meliputi kesalahan prosedur, subjek atau objek hak, tumpang tindih kepemilikan, dan pelaksanaan putusan pengadilan. Penelitian ini memberikan kontribusi dalam memahami mekanisme hukum yang menjamin legalitas kepemilikan tanah dan keadilan administrasi.